Sensor Systems and Software Third International ICST Conference, S-Cube 2012, Lisbon, Portugal, June 4-5, 2012, Revised Selected Papers - Martins, Francisco; Lopes, Luís; Paulino, Hervé (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International ICST Conference on Sensor Systems and Software, S-Cube 2012, held in Lisbon, Portugal in June 2012. The 12 revised full papers presented were carefully reviewed and selected from over 18 submissions and four invited talks and cover a wide range of topics including middleware, frameworks, learning from sensor data streams, stock management, e-health, and Web Of Things.